2014
DOI: 10.1002/pbc.25069
|View full text |Cite
|
Sign up to set email alerts
|

Renal, gastrointestinal, and hepatic late effects in survivors of childhood acute myeloid leukemia treated with chemotherapy only-A NOPHO-AML study

Abstract: Survivors of childhood AML treated with chemotherapy only experienced few renal, gastrointestinal, and hepatic late effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Renal abnormalities have been observed in AML survivors but most were treated with HSCT (Liesner et al, 1994;Leahey et al, 1999). Patients treated with chemotherapy alone have relatively few late renal and gastrointestinal late effects (Skou et al, 2014a).…”
Section: Renal and Gastrointestinalmentioning
confidence: 99%
“…Renal abnormalities have been observed in AML survivors but most were treated with HSCT (Liesner et al, 1994;Leahey et al, 1999). Patients treated with chemotherapy alone have relatively few late renal and gastrointestinal late effects (Skou et al, 2014a).…”
Section: Renal and Gastrointestinalmentioning
confidence: 99%
“…A systematic review of 20 cohort studies investigating hepatic late adverse effects after antineoplastic treatment for childhood cancer is inconclusive . High cumulated doses of anthracyclines are used in acute myeloid leukaemia (AML) but liver diseases are uncommon in non‐transplanted patients . Some studies have suggested that the use of methotrexate induces mild structural changes of the liver that may lead to fibrosis/cirrhosis, although it rarely causes end‐stage liver disease .…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload due to multiple transfusions is common in long‐term survivors . Despite significant iron overload after multiple transfusions in patients without HSCT it is often without signs of liver damage . Iron overload can increase the risk of infections, VOD and hepatic dysfunction …”
Section: Discussionmentioning
confidence: 99%
“…According to a study carried out by Skou et al. () focusing on survivors of AML, 14 (14%) of the survivors experienced recurrent UTIs and 12 (85%) of these are women. In the literature, it is indicated that girls are more prone to UTIs due to some anatomical reasons, such as shorter urethras (Tezer & Ceyhan, ).…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with these problems, it is observed that 67 ( In our study, it was determined that the gender of the children affects the incidence of UTIs and burning and pain during urination, both of which were observed more frequently in women than in men (p < .05) ( Table 5). According to a study carried out by Skou et al (2014) focusing on survivors of AML, 14 (14%) of the survivors experienced recurrent UTIs and 12 (85%) of these are women. In the literature, it is indicated that girls are more prone to UTIs due to some anatomical reasons, such as shorter urethras (Tezer & Ceyhan, 2007).…”
Section: Discussionmentioning
confidence: 99%